The Preparation And Characterization Of Papa Ya Slices And Flour And The Potential Of Flour In Cookie Preparation - Varastegani, Boshra (2014)
Papaya (Carica papaya L.) is one of the important tropical fruits produced in tropical countries around the world. Papaya is rich in nutritional values and has the potential in the production of cookies. The objective of the study was to determine the effects of drying methods on papaya's physico-chemical properties and sensory evaluation. The other objective of the study was to determine the effects of papaya pulp flour's (PPuF) cookies physico-chemical properties and sensory evaluation when partially substituted with wheat flour at 15, 30 and 50 %, respectively. In addition, chemical compositions, antioxidant and functional properties of PPuF were evaluated and compared with commercial wheat flour (WF). The results showed that different drying methods have significant (P<0.05) effects on papaya's physico-chemical properties with 100°C having higher chemical composition, while at 160°C, the papaya slices were higher in antioxidant and total phenolic compounds. Superheated steam drying has the highest values compared to other drying methods.